Crimean Tatar records from Alan Kelly’s catalog - Refat Izzetov (Крымское историческое обозрение, 2022)
The article discusses the issues related to emergence of the first gramophone recordings of the Crimean Tatars at the beginning of the XX century. The list of companies that produced gramophone records with the Crimean Tatar songs and music is given. The article provides an English transliteration of the names of the Crimean Tatar records, which were taken from the catalog of the British scientist, discographer, professor of music at Sheffield University Alan Kelly (1928–2015), indicating recording dates and serial numbers. Finally, the biography of Appaz Sandykchi, one of the performers, is partially restored and presented.